2016
DOI: 10.1186/s12888-016-1020-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, treatment patterns, and patient-related outcomes of patients with Fragile X syndrome in Germany: final results of the observational EXPLAIN-FXS study

Abstract: BackgroundAs data on the phenotype, characteristics and management of patients with Fragile X Syndrome (FXS) are limited, we aimed to collect such data in Germany in experienced centres involved in the treatment of such patients.MethodsEXPLAIN-FXS is a prospective observational (non-interventional) study (registry) performed between April 2013 and January 2016 at 18 sites in Germany. Requirements for patient participation included confirmed diagnosis of FXS by genetic testing (>200 CGG repeats) and written inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…In fact, once behavioral and emotional problems were covaried, our results showed that families with FXS experienced a greater negative impact on feelings about parenting, finances, siblings, and the degree of difficulty of living with a child or adolescent with FXS. In general, our results are similar to those of other studies (Haessler et al, 2016;Johnston et al, 2003;Lewis et al, 2006;Raspa et al 2016).…”
Section: Article In Presssupporting
confidence: 93%
See 3 more Smart Citations
“…In fact, once behavioral and emotional problems were covaried, our results showed that families with FXS experienced a greater negative impact on feelings about parenting, finances, siblings, and the degree of difficulty of living with a child or adolescent with FXS. In general, our results are similar to those of other studies (Haessler et al, 2016;Johnston et al, 2003;Lewis et al, 2006;Raspa et al 2016).…”
Section: Article In Presssupporting
confidence: 93%
“…results are consistent with previous literature (Bailey, 2012;Cordeiro et al, 2011;Haessler, 2016;Newman et al, 2015;Roberts et al, 2014). In general, a defined pattern of problem behaviors, including hyperactivity, inattention, autistic features, and aggression, along with comorbid anxiety, has emerged for this population, and this pattern is estimated to occur in up to 86% of males with FXS (Low Kapalu & Garstein, 2016).…”
Section: Article In Presssupporting
confidence: 92%
See 2 more Smart Citations
“…With a benchmark procedure retrospectively analysing home videos of children with FXS, we, among other researchers, demonstrated that these signs can be readily identified and classified by professionals (Zhang et al 2018; see also Baranek et al 2005). Early phenotypes of FXS present a broad spectrum of atypical neurobehavioural features across various domains (e.g., motor, cognition, speech-language, social-communication), which are not specific to FXS (e.g., Haessler et al 2016; Hagerman 2002; Kidd et al 2014; Marschik et al 2014; Raspa et al 2017; Roche et al 2018; Zhang et al 2017). As early signs of FXS overlap with peculiarities of children with other developmental and genetic disorders, to identify these signs requires sensitivity to deviant development in general and not necessarily expertise in a specific syndrome.…”
mentioning
confidence: 99%